Religious Moderation in Walisongo Material in the Textbook of History and Culture of Islam Class VI Madrasah Ibtidaiyah Ministry of Religious Affairs 2016 - Rofik, Rofik; Pratidinal Jadid, Rosyid (Jurnal Pendidikan Agama Islam, 2021)
This research is focused on the content of religious moderation in Walisongo Material in The Textbook of History and Culture of Islam Class VI Madrasah Ibtidaiyah Ministry of Religious Affairs 2016. This research is motivated by the appeal of the Ministry of Religious Affairs of the Republic of Indonesia that madrasa educational institutions should cover the concept of religious moderation in the textbooks, in this case the History and Culture of Islam. The research method used is qualitative research. The type of this research is library research, more precisely the analysis of textbooks. The results of this study indicate that: (1) Each sub-lesson material of walisongo in the textbook contains indicators of religious moderation (national commitment, tolerance, non-violence, accommodative to local culture), except for Sunan Bonang sub-lessons which do not contain indicators of national commitment and Sunan Giri sub-lessons which do not contain indicators of tolerance. Indicators of religious moderation in Walisongo material can be known with two events. First, directly from the sentence that shows the indicator word itself. Second, the sentence structure of the material is in accordance with the indicator definition. (2) The excess content of religious moderation in walisongo material in the book is that there are indicators of religious moderation contained in the sentence directly and according to the definition of each indicator, and there are illustrations both in the form of pictures and writings, from the real form of religious moderation even though not all of them exist.